Transforming e-government adoption in a framework of innovative civil service of Kazakhstan - Amirova, A.K. (Economic series of the Bulletin of L.N. Gumilyov ENU, 2023)
The empirical research outlined in the article is aimed at identifying citizens’ views on the factors of using e-government portals as part of Kazakhstan’s innovative public service. The article has an exploratory nature. This means that the study takes a new approach to developing an empirically proven, citizen-centered model for e-government implementation. Thus, the article applies several research methods based on deductive approaches, such as content analysis, interview, survey, and factor analysis. From the point of view of Kazakhstan citizens, such factors as «Personal Attitude» and «Trust» to the e-government portal through their readiness have a significant impact on the willingness to use the portal. In this regard, the author has concluded that the client-orientation factors are more important than the technical factors of citizens’ motivation. Overall, the results of the study have focused the work of the government on the key «growth points» of digitalization.